Dynamics of thymol dietary supplementation in quail (Coturnix japonica): Linking bioavailability, effects on egg yolk total fatty acids and performance traits - Fernández, María Emilia (2019)
Phytogenic additives such as thymol are encountering growing interest in the poultry industry. However, there are still questions concerning dynamics of their bioavailability, biological action, optimal dosage and duration of supplementation needed to achieve meaningful effects, as well as persistence of induced changes after supplement withdrawal. We studied the link between the dynamics of free thymol concentration and the changes in fatty acids composition in quail egg yolk, both during a month-long chronic dietary supplementation and after 3 weeks of supplement withdrawal (post-supplementation). Fifty, 85 days-old, female quail of homogeneous body weights (251±1g) in egg-laying peak were used. To evaluate potential dose-dependent effects, three increasing doses 2, 4, and 6.25 g of thymol/kg of feed (THY2, THY4 and THY6, respectively) and two controls were evaluated (n = 10). In parallel, we assessed the concomitant changes in free thymol excretion, potential liver histopathological changes, and birds´ performance traits. Egg yolk and droppings show a dose-dependent increase in THY concentration after 9 days of supplementation and a decrease after post-supplementation. In egg yolk, these changes were accompanied by reduced saturated fatty acid concentrations achieved by 28 days of supplementation in THY2 and 14 days of supplementation in THY4 and THY6. However, after post-supplementation the aforementioned effect disappeared in THY2 but not in THY4 and THY6. While THY2 failed to increase polyunsaturated fatty acids, THY4 and THY6 increased polyunsaturated fatty acids by day 14 of supplementation and remained increased after post-supplementation. Fatty acids changes induced by thymol are consistent with improved nutritional quality of eggs. No treatment effects were observed in liver histopathology and female performance. Findings suggest that both dose of thymol and duration of supplementation modulate thymol and fatty acids concentrations in egg yolk and thymol concentration in droppings. Furthermore, the persistence of those effects after post-supplementation period is also a dose-dependent phenomenon.